Bengali isolated speech recognition : a comparative analysis of the effects of data augmentation on HMM and DNN based acoustic models - Rashid, Warida; Reza, Mohi (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.